Approximate Homomorphisms and Derivations on Normed Lie Triple Systems - Hark-Mahn Kim; Juri Lee (Journal of Function Spaces)
We investigate the generalized Hyers-Ulam stability of homomorphisms and derivations on normed Lie triple systems for the following generalized Cauchy-Jensen additive equation r0f((s∑j=1pxj+t∑j=1dyj)/r0)=s∑j=1p‍f(xj)+t∑j=1d‍f(yj), where r0,s, and  t are nonzero real numbers. As a results, we generalize some stability results concerning this equation.